Creation and creativity in indigenous lowland South America: anthropological perspectives - Halbmayer, Ernst; Goletz, Anne (Berghahn, 2023)
"Investigating local Indigenous processes of creation and creativity, this book uses ethnographic and comparative anthropological perspectives to enquire about creative transformative practices in lowland South America. The volume shows how people create and reinforce their conditions of being by employing different genres of transgression and by creatively shifting contexts of significance. Local socio-cosmic orders, the interrelation of creative genres (myth, verbal art, song, ritual, and handicrafts), and their changing frames of reference (from communal celebrations to wider political and commercial realms) demonstrate the relational, generative, and processual quality of Amerindian creativity"--